Effects of Mechanical Vibration in Neuromuscular Junctions and Fiber Type of the Soleus Muscle of Oophorectomized Wistar Rats - Peretti, Ana Luiza; Kakihata, Camila Mayumi Martin; Wutzke, Maria Luiza Serradourada; Torrejais, Márcia Miranda; Ribeiro, Lucinéia de Fátima Chasko; Bertolini, Gladson Ricardo Flor (Revista Brasileira de Ortopedia, 2019)
Objective To evaluate the neuromuscular junctions (NMJs) and the type of muscle fibers of the soleus muscle of oophorectomized Wistar rats submitted to a mechanical vibration protocol.Methods A total of 36 randomized rats were used in the pseudo-oophorectomy without and with treatment and oophorectomy without and with treatment groups. The treatment was performed with a vibratory platform, frequency of 60 Hz and duration of 10 minutes, 3 times a week, for 4 weeks. At the end of the intervention period, the animals were euthanized and the soleus muscles were collected and processed for analysis of the NMJs and fiber type. The data were analyzed for normality by the Shapiro-Wilk test and analysis of the 3-way variance using the post-hoc Tukey test, when necessary, and a significance level of 5% was adopted.Results In the analysis of the NMJs, the oophorectomy group presented a smaller area than the pseudo-oophorectomy group, but the oophorectomy with treatment group was equal to the pseudo-oophorectomy with treatment group. For the larger diameter of the joints, the oophorectomy group was also different from the others; however, the oophorectomy and treatment animals were larger than those of the pseudo-oophorectomy and treatment group. There was no distinction of the types of fibers, with the muscle presenting fibers of the oxidative type.Conclusion Hormonal deprivation reduced the area and diameter of the NMJs, with reversion of this process in the groups that underwent vibratory platform treatment for 4 weeks, and both surgery and treatment did not influence the type of soleus muscle fiber, composed of oxidative fibers.
Keywords: estrogens; vibration; neuromuscular junction; skeletal muscle